Arapahoe Politics, 1851-1978 - Fowler, Loretta (2025)
The Northern Arapahoes of the Wind River Reservation contradict many of the generalizations made about political change among native plains people. Loretta Fowler explores how, in response to the realities of domination by Americans, the Arapahoes have avoided serious factional divisions and have succeeded in legitimizing new authority through the creation and use of effective political symbols.